History learning as a reinforcement of sustainable development awareness: A literature review - Arditya Prayogi; Riki Nasrullah (Arshaka: Social Sciences and Education, 2025)
Sustainable development is a global agenda that requires the harmonization of environmental, social, and economic aspects to ensure the sustainability of current and future generations. In Indonesia, challenges such as deforestation and social inequality demonstrate the need to increase sustainability awareness through education, especially history learning. This article aims to examine the role of history learning in strengthening awareness of sustainable development. The article was prepared using a qualitative approach through literature study and content analysis, reviewing academic literature relevant to history education and sustainability issues. The results of the review show that historical materials, such as the exploitation of resources in the colonial era, can be integrated with the Sustainable Development Goals (SDGs) to improve students' understanding of sustainability aspects. Context-based approaches and project-based learning can be proven to be capable of encouraging students' critical thinking and proactive attitudes towards environmental and social issues. However, the implementation of this approach is constrained by curriculum density, limited teacher training, and lack of learning resources. Therefore, curriculum revision and teacher training based on Education for Sustainable Development is needed to optimize the role of history education in supporting sustainable development in Indonesia.